Effect of different concentrations of BAP and NAA on shoot regeneration of transgenic broccoli (Brassica oleracea var. italica) - Hamzah, Nurfazira (2014)
Brassica oleracea L. var. italica Plenck (Brassicaceae) is one of the many valuable Brassica species, which is still less cultured under in-vitro condition. The study was conducted to regenerate shoots using petiole explants and to determine the best combination of 6-Benzylaminopurine (BAP) and 1-Naphthalene acetic acid (NAA) for shoot induction in B. oleracea. The explants were obtained from transgenic broccoli plants and placed on shoot induction medium containing basal salts of Murashige and Skoog (MS) supplemented with various concentrations of BAP (0, 1, 3, 5 and 7 mg/L) in combination with various concentrations of NAA (0, 0.05 and 0.1 mg/L). Parameters measured were the percentage of explants regenerating shoots and mean number of shoots per explant. Shoot regeneration was observed every week and data collected after 8 weeks of culture. The study was conducted using Randomized Complete Block Design (RCBD) with 10 replications per treatment. Data were analyzed using Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) was used for comparison of treatment means. The highest percentage of shoot formation (60%) and the highest mean number of shoots produced per explant (21.04) were obtained on medium containing 5.0 mg/L BAP and 0.05 mg/L NAA.